On Weak Graded Rings (European Journal of Pure and Applied Mathematics, 2017)
In this paper, we investigate some properties of weak graded rings that are rings graded by a set G of coset representatives for the left action of a subgroup H on a group X. Moreover a graded rings by using the product H Ã—G are also discussed. A detailed example is given.